Анодні процеси в електрохімічному синтезі метансульфонової кислоти - Матрунчик, Ольга Леонідівна; Тульська, Альона Геннадіївна; Дерібо, Світлана Германівна; Лещенко, Сергій Анатолійович (Дослідно-видавничий центр Наукового товариства ім. Т. Г. Шевченка, 2018)
Synthesis of methanesulfonic acid occurs during the course of an anode reaction – oxidation of dimethyl sulfoxide (DMSO). The application of the electrochemical method of oxidation DMSO allows you to control the process. The control parameters are: the potential of the anode, the catalytic activity of the anode material, the temperature of the electrolyte, promoters and inhibitors in the electrolyte. Voltamperic dependences of methanesulfonic acid from dilute solutions of DMSO with background with sulphate acid were contemplated. The emergence of a half-wave at cyclic voltammetric dependences and the dependence of its limiting current density on the concentration of DMSO indicates the occurrence of adsorption processes. We can talk about the process of oxidation of DMSO to methanesulfonic acid through the intermediate stage of the formation of dimethylsulphone. The possibility of electrochemical synthesis of methanesulfonic acid in a diaphragm electrolyzer with the ratio of the anode current density to the cathode 20:1 is shown.
Anodic processes in the electrochemical synthesis of methanesulfonic acid
Keywords: МСК; диметилсульфоксид; електроліт; пероксид водню; methanesulfonic acid; dimethylsulfone; dimethylsulfoxide; electrochemical synthesis